Social care provided to the families of martyrs in the UAE - ALMansoori, Mariam; Al-Halalat, Khalil (Al-Adab Journal, 2024)
The study aims to identify the role of social care institutions in the United Arab Emirates in providing services to the families of martyrs, which includes clarifying the importance and objectives of social care for the families of martyrs, reviewing government and private institutions that provide social care services to these families, presenting obstacles to providing services, and presenting important proposals to activate the role of social care institutions with the families of martyrs in the United Arab Emirates. The study has revealed many obstacles facing social welfare institutions with the families of martyrs, and the most prominent of these obstacles is the difficulty of obtaining funding and the distance of social care institutions from Islamic references in literature such as solidarity and charity. The study found that creating special funds for spending on the families of martyrs, in-kind and cash donations from businessmen and facilitators, and forming many committees to care for the families of martyrs in some regions of the UAE, providing support for them, and focusing on building community partnerships with charitable and civil institutions are among the most important recommendations of the study.